Wireless Hand - Jenan Staiti; Tasneem Bsharat (My University, 2014)
Abstract                                                                                This project is intended as a project  with Arduino accelerometer, and Bluetooth .                                                                                                                                What this is ??,  this project is a Bluetooth animatronics hand that doesn't need a computer to operate. The user wears a control glove and can control the animatronics hand precisely to move a programmed game via accelerometer .                                                                                                               The game that is programmed, played with moving the hand, up , down, left ,right  .   The idea of game is like the idea of snake game , in this game the player will control of moving the snake using glove.